Kata Majemuk Dengan Unsur Pembentuk Kanji 手 (Te; Shu; Zu) - Lina Rosliana (Diponegoro University, 2019)
This study discusses about “Japanese Compound Noun of Kanji手 (te; shu; zu)”. The purpose of this study is to desbribe the formation process and the meaning of compound noun which formatted by 手 (te; shu; zu) Kanji. The data of this research is obtained from “Shirabe Jisho” digital dictionary. The data were collected with ‘simak’ method and ‘catat’ technique. The data were analysed with ‘agih’ method and ‘bagi unsur langsung’ technique. Based on the analysis of the data, shows that compound noun which formatted by Kanji手 (te; shu; zu) has founded in two meanings, basic meaning and figurative meaning. Basic meaning compoun noun were founded on four kinds of structure, meanwhile figurative meaning of compound noun were founded on five kinds of structure. Kanji手 (te; shu; zu) has nine kinds of meaning when it combines to compoun noun.